Huge Ovarian Cyst Torsion: A Case Report - Maharjan, Sunita (Europasian Journal of Medical Sciences, 2020)
Ovarian cyst torsion (also termed as adnexal torsion) refers to partial or complete rotation of the ovary and a portion of fallopian tube along with its supply to vascular pedicle. It occurs commonly in females of all age group, more on the right side (60%) and often with acute lower abdominal pain lasting for few hours up to 24 hours. Ovarian cyst torsion is one of the devastating conditions hampering blood supply of ovary which may lead to total necrosis of ovarian tissue like in our case. Delayed diagnosis and management can lead to various complications. Here, we present a case of 46 years old perimenopausal female, para 2, living 2 who presented to our emergency department with complain of sudden onset severe pain abdomen since morning. Emergency exploratory laparotomy was done due to high clinical suspicion of torsion based on previous ultrasound finding of ovarian cyst done a day prior to the presentation. On intraoperative finding, the cyst was already necrosed. Due to timely diagnosis and management by emergency laparotomy, anticipated complications were reduced.